2016
DOI: 10.15376/biores.12.1.785-798
|View full text |Cite
|
Sign up to set email alerts
|

Degradable Nursery Containers Made of Rice Husk and Cornstarch Composites

Abstract: The degradation behavior was investigated for eco-composite nursery containers (NCs) prepared with rice husk and cornstarch adhesive modified with urea formaldehyde (UF) as a wet strength agent. The wet shear strength, water absorption capacities, and biological degradation of NCs within soil were also investigated. Quantitative analysis of the thermal degradation behavior of different NC versions was performed by thermo-gravimetric analysis (TGA). The results demonstrated that the introduction of the UF agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The higher content of fixed carbon in stem samples maybe be due to higher lignin, and cellulose content, corresponding to greater vascularization, as it has been reported lignin promotes the production of fixed carbon during pyrolysis 47 . The lower ash content in the stem samples might also influence sample fixed carbon content as ash has a strong catalytic effect to pyrolysis and hampers the generation of fixed carbon 48 .…”
Section: Resultsmentioning
confidence: 79%
“…The higher content of fixed carbon in stem samples maybe be due to higher lignin, and cellulose content, corresponding to greater vascularization, as it has been reported lignin promotes the production of fixed carbon during pyrolysis 47 . The lower ash content in the stem samples might also influence sample fixed carbon content as ash has a strong catalytic effect to pyrolysis and hampers the generation of fixed carbon 48 .…”
Section: Resultsmentioning
confidence: 79%
“…Enhuui Sun et al, took rice husk and corn starch as the main raw materials and prepared biomass seeding trays by urea aldehyde modification, the thermal degradation behavior of different seedling containers was quantified by thermal weightlessness, the results showed that the compound urea formaldehyde-maize starch adhesive is 108.9% stronger than the maize starch adhesive and has good biodegradation properties [ 14 ]. Biomass seeding trays were made using the sunflower seed and rice shell as the substrate by P. Postemsky et al, and evaluated the role of two types of seedling bowl tray in tomato seedling transplanting, cultivate seedlings and production, which showed that the effect of sunflower shell seeding bowl tray on tomato growth and development, flowering and early fruit production were comparable to the control group [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Postemsky et al produced nursery containers from sunflower seed hulls and rice hulls, and the results of seedling trials showed that seedling growth traits of sunflower seed hull seedling containers were better than those of the rice hull seedling container group [13]. Sun E H et al prepared biodegradable ecological composite nursery containers using urea-formaldehyde modified rice hulls and maize starch as the main raw materials, resulting in a 108.9% increase in the dry strength of the nursery trays [14]. Tian M. R. et al mixed rice straw and cow dung with starch adhesive and designed different nursery container models according to the different proportions of raw materials.…”
Section: Introductionmentioning
confidence: 99%